Green ultrasound assisted synthesis of N2,N4,N6-tris ((pyridin-2-ylamino) methyl)-1, 3,5-triazine-2,4,6-triamine as effective corrosion inhibitor for mild steel in 1 M hydrochloric acid medium - Verma C.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
An new corrosion inhibitor namely N2,N4,N6-tris ((Pyridin-2-ylamino) methyl)-1, 3,5-triazine-2,4,6-triamine (INH) was synthesized using green ultrasound technique and its inhibition property on corrosion of mild steel has been studied using gravimetric measurement, Potentiodynamic polarization , electrochemical impedance spectroscopy (EIS) and linear polarization (LR) resistance . Potentiodynamic polarization measurements reveal that this compound effectively suppressed corrosion of mild steel in acid solution and acts as mixed-type inhibitor. EIS plots indicates that the addition of inhibitor increases the charge-transfer resistance (Rct) and decreases the double-layer capacitance (Cdl) of the corrosion process this reveals that investigated inhibitor inhibits mild steel corrosion by adsorption on its surface. The adsorption of inhibitor on the mild steel surface obeys Langmuir adsorption isotherm. © 2013 by ESG.